PERTUMBUHAN PROTOCORM LIKE BODIES ANGGREK CEOLOGYNE CELEBENSIS J.J.SMITH PADA BERBAGAI KONSENTRASI AIR KELAPA SECARA IN VITRO - Wiyatie, .; Muslimin, .; Wahyuni, Dewi (Jurnal Warta Rimba, 2018)
Orchid is one of plants that have econimic value. One of the favorite orchid is Ceoloigyne celebensis J.J.Smith. Ceologyne celebensis is endemic of sulawesi, but research proves if the orchid including extince prone categories so it needs to be preserved.  Propagation of Ceologyne celebensis  will  be done by tissue culture  methode. The growth of orchids will be assisted by providing coconut water as substances growth regulator with some concentrasion. This sutdy aims to determine the effect of coconut water to the shoots and leaves of celogyne celebensis and to know how much of coconut water to be the best concentration. Treatment provide to protocorm is P0=MS + 0 coconut water (Control), P1= MS + 50 ml coconut water, P2= MS + 100 ml coconut water, P3=MS + 150 ml cococnut water, and P4= MS + 200 ml coconut water.Besed research results can be known that 200 ml of coconut water is the best concentration to the growth of orchid ceologyne celebensis . soots appears in 12,2 days and  total of shoots is 1. Leaves appears in 18 days and percentage  of protocorm living is 100%. Keywords: Ceologyne celebensis, Tissue culture, Coconut Water